2020
DOI: 10.1111/cas.14430
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact analysis of treatment‐free remission in nilotinib‐treated Japanese chronic myeloid leukemia patients

Abstract: Treatment‐free remission (TFR), in which patients discontinue pharmacotherapy and remain in molecular remission, is an emerging treatment goal for patients with chronic myeloid leukemia (CML). Attainment of TFR requires an increased frequency of molecular monitoring, to ensure that patients maintain a deep molecular response. The objective of this analysis was to assess the economic impact of stopping nilotinib among Japanese TFR‐eligible patients. A Markov model evaluated the economic impact of TFR among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 37 publications
0
32
0
1
Order By: Relevance
“…Evidence from several studies has shown that molecular monitoring is associated with overall cost savings despite the additional monitoring related costs. A study of 901 Japanese patients eligible for TFR after first- or second-line TKI reported a total cost savings of ¥2,577,451,775, ¥2,589,441,684 and ¥2,458,281,181 during years 1, 2 and 3 (total of ¥7,625,174,640 or US$66,567,775) with 100% compliance to molecular monitoring [ 34 ]. These cost savings persisted with reduced willingness to try TFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from several studies has shown that molecular monitoring is associated with overall cost savings despite the additional monitoring related costs. A study of 901 Japanese patients eligible for TFR after first- or second-line TKI reported a total cost savings of ¥2,577,451,775, ¥2,589,441,684 and ¥2,458,281,181 during years 1, 2 and 3 (total of ¥7,625,174,640 or US$66,567,775) with 100% compliance to molecular monitoring [ 34 ]. These cost savings persisted with reduced willingness to try TFR.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced monitoring of patients may lead to increased disease progression to the AP and BC phases, which are associated with substantial burden and high costs [ 30 ]. Economic analyses have reported reductions in healthcare resource utilization and cost savings with adherence to guideline recommendations for molecular monitoring [ 31 34 ]. However, the cost effectiveness of molecular monitoring in the context of TKI treatment of CML-CP is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Na proposta de descontinuação, é importante que seja garantida a realização desses exames regularmente, uma vez que a avaliação da resposta molecular profunda constitui o principal fator de elegibilidade, além do aumento da taxa de realização do exame durante os primeiros anos após a descontinuação do medicamento para avaliação da remissão ou recidiva da doença. Yamazaki et al (2020), em um estudo de impacto orçamentário da interrupção do uso de nilotinibe no Japão, avaliaram 901 pacientes em um horizonte temporal de três anos, com resultados de US$ 66.567.775,00 (R$ 267.136.481,08 Nota: * Cenário-padrão: referente ao contexto institucional. Cenário 1: variação da recidiva da doença em 60% e 40%, respectivamente.…”
Section: Discussionunclassified
“…Most of the included studies originated in the United States (n = 18, 62%) (42-46, 48, 50-59, 64, 66), followed by Italy (n = 2, 7%) (69,70) and one from each of Brazil (60), the Netherlands (62), France (47), Japan (49), Norway (65), Saudi Arabia (61), Spain (63), and Thailand (67), as well as one multi-country study (58). The studies covered 11 types of cancer including non-small-cell lung cancer (n =8, 28%) (43,45,47,54,55,57,62,65), prostate cancer (n =5, 17%) (42,44,48,59,64), colorectal cancer (n = 4, 14%) (60,67,68,70), ovarian cancer (n = 3, 10%) (46,53,63), breast cancer (n = 2, 7%) (56,61), myeloma (n = 2, 7%) (49,58), melanoma (n = 1, 3%) (52), head and neck cancer (n = 1, 3%) (69), cell carcinoma of the urothelium (n = 1, 3%) (50), gastroenteropancreatic neuroendocrine tumor (n = 1, 3%) (66), and epithelial ovarian, fallopian tube or primary peritoneal cancer (n = 1, 3%) (51). Most of the interventions in these studies involved innovative anticancer drugs, including selective poly ADP-ribose polymerase (PARP)-1 and PARP-2 inhibitor (e.g., niraparib) (51,53), epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 tyrosine kinases inhibitor (e.g., afatinib) (55,…”
Section: Systematic Reviewmentioning
confidence: 99%